Role of Taxane and Anthracycline Combination Regimens in the Management of Advanced Breast Cancer. Issue 17 (May 2015) - Zheng, Ruinian; Han, Shuai; Duan, Chongyang; Chen, Kexu; You, Zhijian; Jia, Jun; Lin, Shunhuan; Liang, Liming; Liu, Aixue; Long, Huidong; Wang, Senming; Corso., Giovanni
<x xml:space="preserve">Abstract</x> Abstract The clinical benefits provided by using combined taxanes and anthracyclines in first-line chemotherapy for metastatic breast carcinoma (MBC) remain uncertain. This meta-analysis compares the benefits of using a combination of anthracyclines along with taxanes versus using single-agent-based chemotherapeutic regimens in the treatment of MBC. Relevant clinical trials as well as abstracts from articles presented at major cancer conferences were searched in various databases including PubMed, Embase, and Cochrane Library. The relevant studies had a primary endpoint of overall survival (OS) and secondary endpoints that included progression-free survival (PFS), time-to-treatment failure (TTF), time to progression (TTP), objective response rate (ORR), disease control rate (DCR), and safety. The hazard ratios of OS, PFS, TTF, and TTP, the odds ratios of ORR and DCR, and the risk ratios (RRs) for grades 1–2 and 3–4 toxicities were extracted from the retrieved studies and analyzed using various statistical methods. Meta-analytic estimates were derived from a random-effect model. Fifteen trials were included in the final meta-analysis, and the results suggest that chemotherapy with combined anthracyclines and taxanes does not significantly improve the OS of MBC patients when compared with the OS achieved using separate taxane or anthracycline-based regimens. Compared with taxane-based regimens, combined taxane along with anthracycline regimens failed to significantly improve TTP, ORR, or DCR, but did significantly improve TTP and ORR when compared with anthracycline-based regimens. Furthermore, both individual taxane-based and anthracycline-based regimens produced fewer toxic reactions compared to combined taxane along with anthracycline regimens. Taxane-based regimens had lower RRs for side effects of neutropenia, infection/febrile neutropenia, nausea, and vomiting, whereas patients receiving anthracycline-based regimens had lower RRs for neutropenia, infection/febrile neutropenia, anorexia, stomatitis/mucosal inflammation, diarrhea, and sensory neuropathy. In contrast, patients receiving taxane-based regimens were at higher RRs for hand–foot syndrome and diarrhea, whereas patients receiving anthracycline-based regimens had higher RRs for nausea and vomiting. A taxane-based treatment regimen may be a better option than a combined taxane/anthracycline regimen for managing patients with advanced breast cancer, as it produces equivalent clinical outcomes and has less toxicity compared to other similar regimens.